Predicting unsafe behaviour from the objective assessment of fatigue manifestation among scaffolders: Evidence from a Quasi-experimental simulation study - Pei Pei Heng; Hanizah Mohd Yusoff; Mohamad Ridza Hj Illias; Yap Jun Fai; Muhammad Fadhli Mohd Yusoff; Norizzati binti Amsah; Rozita Hod (PLoS ONE, 2026)
Background The burden of scaffolding-related accidents was growing. Individual attributes like unsafe behaviour and fatigue have been identified as the important precursors. Understanding the relationship between fatigue manifestation and unsafe behaviour is crucial for developing effective accident prevention protocols. This study aimed to determine the relationship between unsafe behaviour and manifestation of physical and cognitive fatigue during scaffold erection task among scaffolders. Methods A total of 86 scaffolders were recruited into a quasi-experiment with one group pre-post design. Fatigue manifestation was measured objectively at pre-and post-exposure to scaffolding task, employing an assessment protocol consisted of 7 tests. Two fatigue dimensions were evaluated: Physical fatigue (musculoskeletal capacity by hand grip strength, prone plank, trunk flexor endurance and trunk lateral endurance test; postural stability by one leg standing test; joint flexibility by sit and reach test) and cognitive fatigue (simple reaction time test). Throughout the simulation scaffold erection task, unsafe behaviour was rated according to the non-compliance to standard safety protocol. Other independent variables of sociodemographic factors and Pittsburgh Sleep Quality Index score were also included. Results Correlation analysis was significant (p < 0.001) for unsafe behaviour with dominant-hand grip strength (r = −0.57), one leg standing duration with eyes closed (r = −0.69), prone plank duration (r = −0.56), trunk flexor endurance duration (r = −0.61) and reaction time (r = −0.47). Multiple linear regression analysis confirmed the significant predictors of rate of unsafe behaviour including reaction time, one leg standing duration when eye closed, trunk flexor endurance duration and Pittsburgh Sleep Quality Index score. Conclusion These findings will facilitate the development of scaffolding safety protocol for accident prevention, assist industry managers and regulatory decision-makers to govern workers’ safe behaviour via the fatigue mitigation approach.